(untitled) (Stato, Chiese e pluralismo confessionale, 2014)
Contributo sottoposto a valutazione. SOMMARIO: 1. La tutela dei diritti fondamentali all’interno delle confessioni religiose: la tesi e l’ipotesi - 2. Il caso emblematico del Sindicatul Păstorul cel Bun: a) la giurisprudenza rumena - 3. (segue) b) la giurisprudenza della Corte EDU - 4. Autonomia e libertà sindacale: limiti e ordine d’esercizio - 5. Attività ecclesiastiche neutre o non strettamente “spirituali” - 6. Una libertà (sindacale) senza necessità negata. ABSTRACT Freedom of Union inside Religious Organizations. A few comparative Cues. Inside religious Organizations clerics are forbidden to form and to join trade unions. This paper takes its cue from the case of the “Sindicatul Păstorul cel Bun”, to whom Romania refused the registration as a trade union, in order to point out that a few duties practised by priests in favour of their churches are not closely spirituals but rather neutral. Thus, with regard to them, the foregoing ban doesn’t appear as “necessary in a democratic society” under the art. 11 of the European Convention on Human Rights.